Octyl gallate, a food additive with potential beneficial properties to treat: Helicobacter pylori infection - Wolf, Vanessa Gonçalves [UNESP]; Bonacorsi, Cibele; Raddi, Maria Stella Gonçalves [UNESP]; Da Fonseca, Luiz Marcos [UNESP]; Ximenes, Valdecir Farias [UNESP] (Royal Society of Chemistry (RSC), 2017)
Helicobacter pylori infection is marked by intense production of reactive oxygen species (ROS) through the activation of neutrophils that are constantly attracted to the infected gastric mucosa. Here, gallic acid and its alkyl esters were evaluated as compounds able to act as antimicrobial agents and inhibitors of ROS released by H. pylori-activated neutrophils simultaneously. We found that the higher hydrophobicity caused by esterification of gallic acid led to a significant increase in its ability as a cytotoxic agent against H. pylori, a scavenger of ROS and an inhibitor of NADPH oxidase in neutrophils. Octyl gallate, a widely used food additive, showed the highest antimicrobial activity against H. pylori, with a minimum inhibitory concentration (MIC) value of 125 μg mL-1, whereas gallic acid had a MIC value higher than 1000 μg mL-1. The production of superoxide anion radicals was almost 100% abolished by the addition of 10 μM (2.82 μg mL-1) octyl gallate, whereas gallic acid inhibited around 20%. A similar tendency was also found when measuring the production of hypochlorous acid. The protective effect of the esters was cytochemically confirmed. In conclusion, this study showed that hydrophobicity is a crucial factor to obtain a significant anti-ROS and anti-H. pylori activity. Finally, it highlights octyl gallate, a food additive widely used in the food industry, as a promising molecule in the treatment of H. pylori infection.